Juridical Analysis of Minors' E-Commerce Transactions Are Related To Article 1320 of the Civil Code's Agreement Terms - Aditya Algifari Badu; Mutia Cherawaty Thalib; Abdul Hamid Tome (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to determine the validity of the Terms of Agreement on Transactions through e-commerce conducted by minors, which is divided into two sub-discussions, namely first how the validity of agreements in e-commerce transactions according to Article 1320 of the Civil Code and second how the legal protection of the parties in conducting e-commerce transactions conducted by minors. This type of research is a qualitative literature research with a juridical-normative approach. The results of this study show that agreements through e-commerce are declared valid and declared born when an agreement is reached regarding the object being promised, and cannot be separated from what has been basically stated by Article 1320 of the Civil Code by using electronic media so that the contract is not realized in writing. E-commerce transactions are carried out by parties, one of which is under age, the agreement is considered valid as long as it does not harm both parties, and the underage party understands the agreement that must be fulfilled and is responsible for what has been agreed upon.